2022
DOI: 10.4269/ajtmh.21-0597
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Household Knowledge and Practices during a Cholera Epidemic— Dar es Salaam, Tanzania, 2016

Abstract: From August 15, 2015 to March 5, 2016, Tanzania reported 16,521 cholera cases and 251 deaths, with 4,596 cases and 44 deaths in its largest city, Dar es Salaam. To evaluate outbreak response efforts, we conducted a household survey with drinking water testing in the five most affected wards in Dar es Salaam. We interviewed 641 households 6 months after the beginning of the outbreak. Although most respondents knew that cholera causes diarrhea (90%) and would seek care if suspecting cholera (95%), only 45% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…Furthermore, a majority of respondents showed satisfactory/fair levels of cholera knowledge regarding the items tackling the preventive measures. Our results contrast those from several KAP studies in the context of cholera, which showed a generally poor level of knowledge in countries including Bangladesh [ 22 ], Saudi Arabia [ 17 ], Yemen [ 24 ], Democratic Republic of Congo [ 47 ], and Tanzania [ 48 ]. On the other hand, a qualitative study from South Africa showed better levels of cholera knowledge, likely related to previous reporting of several outbreaks in the country [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, a majority of respondents showed satisfactory/fair levels of cholera knowledge regarding the items tackling the preventive measures. Our results contrast those from several KAP studies in the context of cholera, which showed a generally poor level of knowledge in countries including Bangladesh [ 22 ], Saudi Arabia [ 17 ], Yemen [ 24 ], Democratic Republic of Congo [ 47 ], and Tanzania [ 48 ]. On the other hand, a qualitative study from South Africa showed better levels of cholera knowledge, likely related to previous reporting of several outbreaks in the country [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our data showed that 95.7% of participants knew the most common and characteristic symptom of cholera “watery diarrhea”. This is comparable to previous studies where cholera is endemic [ 13 ]. The average total knowledge in the current study was 40.39%; it is suboptimal.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies from other countries have described single-entity items for practices toward cholera. In Tanzania, water treatment with chlorine was rarely applied to prevent infection [41]. The use of oral rehydration solution (ORS) in the management of acute illness to prevent dehydration among their population was also scarce.…”
Section: Discussionmentioning
confidence: 99%